Afro-descendants, body and nation in Argentina: a literature based (1837-1882) - Guevara Jaramillo, Nathalia (Cultura y Representaciones Sociales, 2019)
In this paper, I explore the representations of afro-descendants’ bodies in a set of publications from Argentina’s national literature. I then examine the points of view of a group of afro-descendant poets from Buenos Aires with regard to the representations produced by the members of the political and intellectual elites of the country. Representations on the body and the biopolitical function in elite literature allow us to approach the conjunction of race and the construction of nation in Argentina.